2020
DOI: 10.3906/zoo-1904-1
|View full text |Cite
|
Sign up to set email alerts
|

First record of Ahaetullamycterizans (Linnaeus, 1758) (Serpentes: Colubridae) from the Lesser Sunda region, Indonesia, based on molecular and morphological identification

Abstract: The arboreal snake genus Ahaetulla (Link, 1807) is composed of 8 species distributed in most countries of the Asian region, including Indonesia,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Due to the unavailability in the Genbank dataset of the sequences of Indahsari et al (2020) from the topotypical Javan population of A. prasina, we are unable to include the Javan population in our phylogenetic analysis and cannot calculate the genetic distance directly from the Javan population. Nevertheless, the Sundaic population (Indahsari et al 2020) and the Northeast Indian population (current study) are both deeply divergent from the Thai population which lies geographically between the two. We found that the Northeast Indian population differs from the South Chinese population by 6.7%, from the Thai population by 6.3% and from the Vietnamese population by 7.4% at Cytb (Table 5a).…”
Section: Molecular Phylogeneticsmentioning
confidence: 57%
See 4 more Smart Citations
“…Due to the unavailability in the Genbank dataset of the sequences of Indahsari et al (2020) from the topotypical Javan population of A. prasina, we are unable to include the Javan population in our phylogenetic analysis and cannot calculate the genetic distance directly from the Javan population. Nevertheless, the Sundaic population (Indahsari et al 2020) and the Northeast Indian population (current study) are both deeply divergent from the Thai population which lies geographically between the two. We found that the Northeast Indian population differs from the South Chinese population by 6.7%, from the Thai population by 6.3% and from the Vietnamese population by 7.4% at Cytb (Table 5a).…”
Section: Molecular Phylogeneticsmentioning
confidence: 57%
“…But sightings of the buff variety prompted Wall to discuss their taxonomy, putting weightage on colour differences. However, based on the current understanding of distributions, it seems that geographic barriers may have prompted the cryptic diversification of the A. prasina complex across its range (also see Indahsari et al 2020). Our work on these A. prasina populations further emphasizes the underappreciated role of geographic disjunction, coupled with cryptic morphology covering the underlying deep genetic divergence that has rendered the status of the A. prasina group, and other similar groups, so challenging.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations